CODE OF POINT AND RUBRIC EVALUATION OF GYM IN LEARNING JASMANI EDUCATION IN SCHOOL - Tono Sugihartono (DHARMA RAFLESIA, 2020)
Code of points, an artistic gymnastics competition assessment guideline set out in the gymnastics competition's rule book that governs the regulation of the assessor's tasks, stages, and levels of gymnast's age and its characteristics both junior and senior. The purpose of the code of point is, 1) that the junior gymnast can develop up to the peak of achievement at the senior level, 2) so that the gymnast can perform safely and avoid injuries that interfere with the physical development of the gymnast, 3) so that the assessment can be carried out with the same guidelines and not to be misunderstood. The target audience of community service are PJOK teachers both who work in the elementary, junior high school education units and as gymnastic trainers. The results of the activity show that the teachers and trainers have mastered the code of point assessment in gymnastic learning, so that the teacher is able to 1) solve the problem by examining the series of gymnastic movements at Olimpiade Olahraga Siswa Nasional(O2SN) branch exercises, 2) mastering the sign of body parts if there are mistakes in making the movement so that the value is reduced; 3) understand the level of small, medium and large errors, specifically about bending angle errors of less than 150, bending angles between 150 to 300, and bending with angles of more than 300. 4) assessing aesthetic elements in carrying out movements, including flexibility of motion, structuring the movements in shaping synchronization (specifically for female gymnasts to harmonize with accompaniment music), order and structure of movements. 5) able to assess movements that contain special requirements (requirment) in the artistic gymnastics of the floor such as there must be an acrobatic element, a gymnastic element, the press balance element persists for a certain time.